Antioxidant/reducing properties of the extracts from the genus Vítex plant leaves - Laguta, I.V.; Fesenko, T.V.; Stavinskaya О.N.; Levchyk, N.Ya.; Dzyuba О.I. (Reports of the National Academy of Sciences of Ukraine, 2017)
Ethanol extracts from Vitex cannabifolia, Vitex agnus-castus, and Vitex negundo leaves are prepared, and the antioxidant/reducing properties of the extracts are investigated. All the extracts are found to contain a significant amount of phenol antioxidants, including flavonoids, and possess the high ability to reduce both DPPH radicals and Ag+ ions. The activities of the extracts in the reaction with DPPH radicals and in the "green" synthesis of silver nanoparticles differ from each other and correlate with the flavonoid content and total phenol content, respectively.